2013
DOI: 10.3758/s13423-013-0391-6
|View full text |Cite
|
Sign up to set email alerts
|

On the (non)persuasive power of a brain image

Abstract: The persuasive power of brain images has captivated scholars in many disciplines. Like others, we too were intrigued by the finding that a brain image makes accompanying information more credible (McCabe & Castel in Cognition 107:343-352, 2008). But when our attempts to build on this effect failed, we instead ran a series of systematic replications of the original study-comprising 10 experiments and nearly 2,000 subjects. When we combined the original data with ours in a meta-analysis, we arrived at a more pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
85
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(95 citation statements)
references
References 24 publications
7
85
1
2
Order By: Relevance
“…That the findings of Weisberg et al (2008) can still be successfully replicated suggests that this is not the case (Michael et al, 2013). Instead, it seems that neuroscience evidence may enhance the credibility of poorly reasoned arguments, even if brain images per se do not.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…That the findings of Weisberg et al (2008) can still be successfully replicated suggests that this is not the case (Michael et al, 2013). Instead, it seems that neuroscience evidence may enhance the credibility of poorly reasoned arguments, even if brain images per se do not.…”
Section: Discussionmentioning
confidence: 92%
“…Michael et al (2013) conducted 10 direct replications of McCabe and Castelʼs (2008) Experiment 3. A meta-analysis including these and McCabe and Castelʼs original results found that brain images exerted "little to no influence" on judgments of credibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent work has not yet identified the mechanism by which neuroscience content may have this effect. Although early evidence suggested that neuroscience images influence people's judgments (McCabe & Castel, 2008), these results have failed to replicate (Gruber & Dickerson, 2012;Michael, Newman, Vuorre, Cumming, & Garry, 2013;see Farah & Hook, 2013 for a review). Additionally, neuroscience jargon (e.g., ''fMRI imaging") has no effect over and above references to the brain in plain language (e.g., ''brain scans": Weisberg et al, 2015, Study 3).…”
Section: Introductionmentioning
confidence: 92%
“…Jurors are more likely to be swayed by physical (trace) evidence such as shoeprint evidence, for instance, than by eyewitness testimony (Skolnick & Shaw, 2001; see also Ask, Rebelius, & Granhag, 2008). Research also suggests that people find neuroscience explanations persuasive, possibly because such accounts provide evidence of a link between brain activity and behavior (Gurley & Marcus, 2008;Weisberg, Keil, Goodstein, Rawson, & Gray, 2008; see also Michael, Newman, Vuorre, Cumming, & Garry, 2013 for limitations of persuasive neuroscience evidence). Together these studies suggest that people perceive physical evidence to be extremely reliable.…”
Section: The Reliability and Cost Of Informationmentioning
confidence: 99%